PENENTUAN INDEKS AKTIVITAS MATAHARI EKSTRIM HARIAN - - Jiyo; Sri Suhartini (Lembaga Penerbangan dan Antariksa Nasional, 2005)
In this paper we discuss a method to determinated extreme solar activity index (ESAI) which refer to X-ray (SXR) flare. ESAI-index is calculated by using the simple methods with the inputs are intensity and duration of SXR- flare. From the case study of solar storm at middle January 2005, ESAI-index is better for showing the solar activities impact to ionosphere. However, it still need further study by adding more spatial and temporal data.